The multimodality of children’s artefacts: towards a toy literacy - Almeida, Danielle Barbosa Lins (Calidoscópio, 2023)
Whether toys are made of metal, plastic, leather, fabric, wood or any soft material, they seem to reveal cultural references and evoke emotional reactions. The aim of this article is to expand the agenda of childhood studies (Caldas-Coulthard & van Leeuwen, 2001, 2002, 2004; Machin and van Leeuwen, 2009; Almeida, 2006; 2008; 2009; 2014; 2017; 2018; 2020; 2021), which have been effective as theoretical tools to toys’ semiotics from a two-dimensional, linguistic perspective. The idea is to offer a tool to check on toys’ material configurations such as texture, smell, kinetic possibilities and the degree of realism of these three-dimensional childhood representations by constructing a multimodal framework – which I have called toy literacy – to analyse toys in their three-dimensional features. Through the verbal and visual choices behind toys’ design, packages and campaigns we can discuss some of the roles provided by their multimodal messages and reflect upon the kind of childhood which is constructed through their material representations. By means of a metalanguage, I have created a framework that may be of help to different social sectors – from the academic to the more general public. In providing a systematic language to talk about toy choices, I hope to promote reflection on the social structures pertaining to toys’ gender and cultural representations, which, for long, have been kept concealed. Keywords: Toys; Multimodality; Materiality.